2007
DOI: 10.3351/ppp.0001.0002.0005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and identity: homeless women’s use of public spaces

Abstract: Abstract AbstractThis paper explores women's geographies of homelessness with a particular focus on homeless women's use of public spaces in England. It demonstrates that homeless women's spatial boundaries are not confined to the institutional spaces of homelessness, as much literature and research would suggest, but frequently extend into public spaces and buildings. The paper also argues that homeless women's use of public spaces can be conceptualised in terms of resistance: by occupying these spaces homele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similarly, Magee and Huriaux (2008) found that homeless women felt isolated due to limited contact with housed family and friends and they also experienced societal alienation and discrimination from living in shelters. Casey, Goudie, and Reeve (2007) study concerning homeless women and the use of public spaces in Britain found that given the high level of restriction placed on the environments where homeless individuals make their habitats and go about their daily lives, the homeless feel a great deal of social exclusion from public spaces, which may lead to feelings of detachment from the community. Importantly, Fast, Small, Krüsi, Wood, and Kerr (2010) have found that the more individuals become detached from mainstream society, the less likely it becomes that they will leave their lives on the streets.…”
Section: Street-involved People's Social Relationshipsmentioning
confidence: 99%
“…Similarly, Magee and Huriaux (2008) found that homeless women felt isolated due to limited contact with housed family and friends and they also experienced societal alienation and discrimination from living in shelters. Casey, Goudie, and Reeve (2007) study concerning homeless women and the use of public spaces in Britain found that given the high level of restriction placed on the environments where homeless individuals make their habitats and go about their daily lives, the homeless feel a great deal of social exclusion from public spaces, which may lead to feelings of detachment from the community. Importantly, Fast, Small, Krüsi, Wood, and Kerr (2010) have found that the more individuals become detached from mainstream society, the less likely it becomes that they will leave their lives on the streets.…”
Section: Street-involved People's Social Relationshipsmentioning
confidence: 99%
“…In view of Goffman's (1959) theory of identity, the women's actions might be based on a strong feeling of dissonance between their felt personal identity and the social construction of the homeless "dirty bearded male" (Williams, 2001). This dissonance is also evident in the women's accounts of their interaction with the public, a finding documented in studies exploring perceived stigmatisation in the UK homeless women (Casey et al, 2007(Casey et al, , 2008 and which requires further research to explore. Goffman (1959) stated that identity is formed through social interaction, and it is possible that the women's degrading interactions with the public compound difficulties they already have with holding on to their personal identities.…”
Section: Discussionmentioning
confidence: 98%
“…A lack of homeless services makes spaces like public parks essential resources and places of refuge for unsheltered people. Casey et al (2007) found unsheltered women preferred public spaces to institutionalised environments because they were practical, positive spaces in which to live and survive. Those who experience unsheltered homelessness use creativity to avoid contradicting the informal rules of public space by blending in, disguising socially unacceptable activities, limiting belongings, and avoiding peak business hours (Casey et al, 2007;Rose, 2017).…”
Section: Urban Parks and Homelessnessmentioning
confidence: 99%
“…Casey et al (2007) found unsheltered women preferred public spaces to institutionalised environments because they were practical, positive spaces in which to live and survive. Those who experience unsheltered homelessness use creativity to avoid contradicting the informal rules of public space by blending in, disguising socially unacceptable activities, limiting belongings, and avoiding peak business hours (Casey et al, 2007;Rose, 2017). These societal barriers reinforce Taylor et al's (2007) call for an EJF as a way to critically examine mitigation strategies in an effort to develop park management plans reflective of the health and recreational needs of an entire community.…”
Section: Urban Parks and Homelessnessmentioning
confidence: 99%